2007
DOI: 10.1063/1.2780151
|View full text |Cite
|
Sign up to set email alerts
|

A single particle model to simulate the dynamics of entangled polymer melts

Abstract: We present a computer simulation model of polymer melts representing each chain as one single particle. Besides the position coordinate of each particle, we introduce a parameter n(ij) for each pair of particles i and j within a specified distance from each other. These numbers, called entanglement numbers, describe the deviation of the system of ignored coordinates from its equilibrium state for the given configuration of the centers of mass of the polymers. The deviations of the entanglement numbers from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
96
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(97 citation statements)
references
References 41 publications
1
96
0
Order By: Relevance
“…More recently, the method has been extended to chains of Gaussian blobs by Pierleoni and his co-workers [253,254] and Kremer and his co-workers [255,256], allowing for much more efficient implementations. Kindt and Briels [86] developed a single-particle model to study entangled polymer chain dynamics. In this model, the entanglement number, n ij , is introduced between particle pairs, i and j, which accounts for the deviation of the the ignored degrees of freedom from the equilibrium state.…”
Section: Super Coarse-graining Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, the method has been extended to chains of Gaussian blobs by Pierleoni and his co-workers [253,254] and Kremer and his co-workers [255,256], allowing for much more efficient implementations. Kindt and Briels [86] developed a single-particle model to study entangled polymer chain dynamics. In this model, the entanglement number, n ij , is introduced between particle pairs, i and j, which accounts for the deviation of the the ignored degrees of freedom from the equilibrium state.…”
Section: Super Coarse-graining Methodsmentioning
confidence: 99%
“…The displacements of the centers of mass of polymer chains are governed by these transient forces and the conservative forces originating from the potential of mean force. The equilibrium entanglement number, n 0 (r ij ), is set as [86]:…”
Section: Super Coarse-graining Methodsmentioning
confidence: 99%
“…It is shown that strong links have the property that they are sampled at least once within this time interval. By following the space-time trajectories of selected links, under equilibrium, deformation, or flow, we could obtain useful mesoscopic information for the development of hierarchical sliplink, or single particle [93][94][95] simulation schemes. The mean square displacement of selected links is presented in the appendices.…”
Section: Introductionmentioning
confidence: 99%
“…Then a choice has to be made: either to coarsegrain further but somehow maintain the information about entanglements, or to switch to one-chain models. The …rst method has been most successfully pursued by the group of Wim Briels, who suggested either preventing chain crossing geometrically [9], or maintaining information about entanglements by re-introducing slow variables such as the number of entanglements between two coils [10]. On the other hand, a one chain model can eventually lead to the tube model, which can be simpli…ed to a constitutive equation [11].…”
mentioning
confidence: 99%